Political fragmentation and fiscal policy: Evidence from German municipalities - René Bernard (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2017)
The government fragmentation hypothesis (GFH) states that coalition governments spend more than single-party governments due to an underlying common pool problem. Using a large panel data set on 604 local governments in the German state of Baden-Württemberg for the 1994-2014 period, I test the GFH for tax rates, the growth in government debt as well as expenditures and its sub-categories. Studies using standard regression methods fail to identify causal effect as the type of government is generally not random. I apply a RDD, that exploits quasi-random variation generated by close elections. I add external validity to the recent quasi-experimental literature by investigating the GFH for a mayor-council system. I find that contrary to the theoretical prediction, coalition governments do not increase taxes and government debt. There is a non-robust, negative effect on total expenditures, which is mainly driven by administrative expenditures and material expenditures. – – Die Regierungsfragmentierungs-Hypothese (GFH) konstatiert, dass Koalitionsregierungen auf Grund eines Common Pool Problems höhere Staatsausgaben aufweisen als Einparteienregierungen. Ich teste die GFH für die kommunalen Steuersätze, das kommunale Schuldenwachstum und die kommunalen Ausgaben unter Verwendung eines Panel-Datensatzes, der 604 Baden-Württembergische Kommunen für den Zeitraum von 1994-2014 umfasst. Da der Regierungstyp generell nicht zufällig ist, können Studien, die herkömmliche Regressionsmethoden verwenden, den kausalen Effekt nicht identifizieren. Ich verwende ein Regressions-Diskontinuitäts-Design, das die quasi-zufällige Variation knapper Wahlausgänge ausnutzt, und trage zur neuen quasi-experimentellen Literatur bei, indem ich die GFH im Kontext einer Bürgermeisterverfassung analysiere. Entgegen der theoretischen Vorhersage erhöhen Koalitionsregierungen weder die Steuersätze noch die Verschuldung. Koalitionsregierungen haben einen nichtrobusten, negativen Effekt auf die Bruttoausgaben, der im Wesentlichen von den Verwaltungsausgaben und dem Laufenden Sachaufwand getrieben ist.
Keywords: C21; D72; D78; H11; H71; H72; 330; government fragmentation; common pool problems; legislative policy-making; government spending; local fiscal policy; local taxation; local elections; municipality data; regression discontinuity design; Fragmentierung der Regierung; Common Pool Problem; Gesetzgebung und politische Entscheidungsfindung; Staatsausgaben; kommunale Finanzpolitik; kommunale Steuern; Kommunalwahlen; Gemeindedaten; Regressions-Diskontinuitäts-Design